Biological treatability processes of textile wastewaters using electrocoagulation and ozonation - Avsar, Yasar; Kabuk, H. Akif; Kurt, Ugur; Cakmakci, Mehmet; Ozkaya, Bestamin (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2012)
This study presents biotreatment of textile wastewaters using electrocoagulation and ozone processes. Ozonation process gave better results than electrocoagulation process. For electrocoagulation, optimum working conditions were found as follows: pH, 6.5; electrode type, iron electrode; current density, 20 mA/cm(2); and reaction time, 15 min. Under these circumstances, values determined for electrocoagulation and ozonation processes, respectively, were as follows: COD removal, 73, 46%; color removal, 85,93%; BOD/COD ratio, 0.60, 0.69; and cost per unit of wastewater treatment, 1.7, 1.3 $.
Keywords: Biological treatability; Electrocoagulation; Ozonation; Textile wastewater; WASTE-WATER; OXIDATION; DYE; Engineering